Do rewards work? Evidence from the randomization of public works - Paul E. Carrillo; Edgar Castro; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2017)
This paper evaluates the effect of positive inducements on tax behavior by exploiting a natural experiment in which a municipality of Argentina randomly selected 400 individuals among more than 72,000 taxpayers who had complied with payment of their property tax. These individuals were publicly recognized and awarded the construction of a sidewalk. Results indicate that: i) being selected in the lottery and publicly recognized by the government has a positive but not persistent effect on future compliance; ii) receiving the sidewalk has a large positive and persistent effect; iii) high and persistent spillover effects exist: some neighbors of those who receive the reward comply more too, and these effects can be even larger than the direct effects; and iv) there is no financial motive effect; i.e., people do not pay their taxes just to participate in the lottery. Recognition serves only as a short-term incentive, but the provision of a durable and visible good has more persistent and broader effects. These findings provide evidence on features that make a positive inducement more successful, whether for tax compliance or other policy purposes.
Keywords: C93; H42; H23; D62; 330; Rewards; Positive incentives; Persistence; Spillovers; Tax compliance; Public goods; Public policy